Evaluation of Aphid Resistance and Oleoresin Production in Indigenous Tropical Pine (Pinus merkusii Jungh. and de Vriese) - Purwanto, Purwanto (MDPI, 2022)
The native tropical pine (Pinus merkusii Jungh. and de Vriese) has been genetically improved in Indonesia since 1977; nevertheless, minor evaluations of aphid resistance have been conducted since 2004. As a result, a progeny test for aphid resistance was established in 2010 in Lawu, Central Java, Indonesia. Subjects in the trial were attacked significantly at the rate of 30.7% after 4 years, but surprisingly, some individuals were found to be healthy without any aphid attack. The observed a 7-year progeny trial comprised 34 families with 4 trees per unitary plot and replicated in 10 blocks. At 7 years, observations during 9 months (April–December) showed that there were differences in the range of resistance across families. The stem diameter, oleoresin production, and resistance to aphid attack were evaluated, and all traits were distinct among families except for oleoresin exudation from the western side of the stem. Five families performed above average for all three traits, while three other families had high diameter and maintained good oleoresin production. These eight families can be included in a forward selection strategy. Cluster analysis revealed that the eight best families were grouped into two of the eight clusters. Phenotypic correlations revealed that all pairs of traits were significantly related, with the highest correlation registered between stem diameter and resistance to aphid attack (0.99). Forward selection ensures the simultaneous improvement of the three traits.